Innovating animation teaching system: an experimental survey on the integration of design thinking and creative methods for animation education in China - Abd Manan, Mohd Shahrudin; Wang, Xuefeng; Tang, Xi (Scientific Research Publishing, 2022)
This paper discusses outcomes from an experimental survey on the integration of Design Thinking (DT) and Creative Methods (CM) for animation education in Chinese universities. The survey was conducted on 62 college students at two different universities, namely, Kunming University in Yunnan and Hunan University of Science and Engineering in Hunan. Two experimental stages, pretest and posttest experiments, were adopted in the completion of the survey. In understanding the teaching effect of DT and CM, an analysis was performed based on six parameters: Familiarity, Performance, Ability, Time, Reference, and Attitude. The analytical findings thus become a basis for the development of an integrated Animation Teaching System as a pedagogical approach in animation education.